Role conflict and confidentiality in multidisciplinary athlete support programmes. Issue 3 (1st June 1999) - Collins, D; Moore, P; Mitchell, D; Alpress, F
Abstract : As medical and scientific staff have increasingly been called upon to provide multidisciplinary support to elite performers the potential for ethical, professional, and legal conflicts has also increased. Although this has been recognised, little guidance has been provided to help resolve such conflicts. This paper identifies key issues in the provision of effective support and specifically addresses the roles of medical and scientific staff and their relations to coaches and performers. An athlete charter is presented that has successfully been used to resolve ethical conflicts and clarify the lines of communication, confidentiality, and responsibility within a national governing body.